Active vibration control of a beam with piezoelectric patches: real-time implementation with xPC target - Abdul Muthalif, Asan Gani; Salami, Momoh Jimoh Emiyoka; Khan, Md. Raisuddin (2003)
Active control of a vibrating beam using smart materials such as piezoelectric materials is examined in this paper. A model based on Euler-Bernoulli beam equation has been developed a n d . then extended with bonded three piezoelectric patches which act as sensor, actuator and exciter. The sensor and actuator are collocated to achieve a minimum phase. The aim of this research work is to control the first three resonant modes. To achieve this, a compensated inverse PID controller is developed and- tuned to damp these modes using MATLAB. The designed controller for damping each mode is then combined in parallel to damp any of the three modes. Finally, the simulation results are verified experimentally and the real-time implementation is carried out with XPC target toolbox in MATLAB.